CONSTRUCTION AND VALIDATION OF A CLINICAL SIMULATION ON HIV TESTING AND COUNSELING IN PREGNANT WOMEN - Melo, Matheus Santos; Llapa-Rodriguez, Eliana Ofelia; Bispo, Laura Dayane Gois; de Andrade, Joseilze Santos; Barreiro, Maria do Socorro Claudino; de Resende, Luana Teles; Rodrigues, Iellen Dantas Campos Verdes (Cogitare Enfermagem, 2022)
Objective: to construct and validate a clinical simulation scenario on rapid HIV testing and counseling in pregnant women. Method: methodological study, of appearance and content validation, developed between June and October 2020 through the Delphi technique. For validation, the judges who obtained five or more points according to the adapted Fehring criteria were included. The data were analyzed by calculating the Content Validity Index (CVI). Results: After the first Delphi round, two items (5.7%) did not reach the I-CVI required for validation in all the criteria evaluated, which were: behavioral, objectivity, simplicity, clarity, relevance, accuracy, variety, modality, typicality, and credibility. At the end of the second Delphi round, all items (100%) reached the I-CVI required for validation. Conclusion: the script proved to be valid, contributing to subsidize the teaching of HIV testing and counseling of pregnant women.